Specificity of insect-plant associations and their role in the formation of plant defenses and speciation - Volf, Martin (Jihočeská univerzita, 2016)
The aim of this dissertation is to investigate what role insect-plant interactions play in the formation of host-plant defenses and in the diversification of both groups. We show that various groups of herbivore respond differently to host-plant defenses. Therefore plant defenses diversify into suites of complementary traits, as individual traits fail to provide protection against specialized herbivores. Further, we identify what levels of host-phylogeny shape the food-web structure of insect herbivores. We show that specialized herbivores are affected mainly by the terminal parts of the host-phylogeny. In contrast, more polyphagous guilds are affected mainly by the mid-levels of the host phylogeny because the effects of terminal or deeper phylogeny seem to be surpassed by other factors in more generalist insect species. In the last chapter, we show how specialized insect-plant interactions generated by tight insect-plant coevolution can influence the speciation in plants over environmental gradients.
Specificity of insect-plant associations and their role in the formation of plant defenses and speciation
Keywords: coevolution; Ficus; herbivory; defensive traits; insect communities; Salix; secondary metabolites; speciation; coevolution; Ficus; herbivory; defensive traits; insect communities; Salix; secondary metabolites; speciation